Infection COVID-19 chez la femme enceinte: à propos d’un cas - Kouas, Sofiane (Pan Afr Med J, 2020)
The recent COVID-19 pandemic has led to an unprecedented global health crisis. The susceptibility of pregnant women to infections has raised many questions about the risk of transmission, teratogenic risk and maternal and fetal complications. The speed at which the infection advanced as well as the ambiguity effects on pregnancy, due to the absence of scientific data, led obstetricians to adapt their practice according to pragmatic approach. We focused on this subject declared by the WHO as a global pandemic in early March 2020 to develop a plan for obstetric management of SARS-CoV-2 infected patients on the basis of current data. Based on the literature and the case of a patient hospitalized in our Department of Gynecology in Mahdia, the purpose of this study was to describe the possible clinical manifestations of COVID-19 infection in pregnant women and to develop principles of management of patients with COVID-19 infection.